Breathing inequality? Income, ethnicity and PM2.5 exposure in Bologna, Italy - Alessandra Drigo (Fondazione Eni Enrico Mattei (FEEM), 2024)
This study addresses the presence of an environmental justice issue along the dimensions of income and ethnicity in the urban context of Bologna, Italy. Among other Italian cities, Bologna has historically had a left-leaning political tendency and has made considerable substantial efforts to address social issues extensively. This makes it a useful cross-section dataset links gridded PM2.5 concentration data at 0.01êx0.01ê resolution with census demographic characteristics and income per capita information for the year 2011. This study presents two main findings. i) it confirms the existence of an environmental justice gap, which affects vulnerable segments of the population along both income and ethnicity dimensions. A 1% increase in income per capita is associated with a 0.09% decrease in PM2.5 levels (a rise of 1 standard deviation of income per capita in the census corresponds to a reduction of -0.53 mg/m3 in PM2.5); whereas a 1% increase in the share of non-white individuals living in the census tract leads to a 0.13% increase in PM2.5 levels (+3.92 mg/ m3 increase associated with a rise of 1 standard deviation in the proportion of non-whites in the census). ii) There is currently no evidence to suggest that exposure disparities for nonwhite individuals are changing depending on income level, whether it is lower or higher. Residence in lower/higher income areas of the city does not significantly exacerbate/ alleviate these disparities for non-white communities. Overall, these results highlight the widespread occurrence of environmental injustice across various geographical and political settings, including those that have historically prioritized social concerns.
Keywords: Q53; Q56; I14; C21; 330; Environmental inequality; Environmental justice; Air pollution; Racial disparities; Socioeconomic status